A matemática, o quadro de escrever e os formadores de professores de matemática: interpretando relações - SANCHES, Ana Claudia de Melo (Universidade Federal do Pará, 2012)
For a long time the printing board or blackboard was the reference of a traditional education, was only to demonstrate and to symbolize the teaching knowledge teaching knowledge, a time that to the teachers the condition of detainer of knowing perpetuated and transmitter of all knowledge that enjoy, without the least to reflect importance and meanings of the use of the picture in function the collective construction of the knowledge intermediated for the picture to write. To demystify these estimated it was the proposal of this study, a time that if it searched to understand which excellent and differentiated aspects that the professors of mathematics teachers attribute to the use of the picture. The same the time where they need to take care of the perspectives of century XXI. In a focal inquiry we look for to identify together to the narratives of constitution of the professors personal and collective influences in relation to the teaching and to knowledge developed in relation to the use of the picture. Since by some times and in different speeches the picture was remembered as “bulk memory only ” of the construction of the mathematical reasoning. The quarrels carried through here about had been based on data collected through questionnaire interviews, which have as priorities the teaching formation and its relations with the picture to write. Beyond the relevance of the picture to write in the education of the mathematics and the formation of critical and mediating teachers of mathematics.